Dissociative Experience and Cultural Neuroscience: Narrative, Metaphor and Mechanism - Seligman, Rebecca (Cult Med Psychiatry, 2008)
Approaches to trance and possession in anthropology have tended to use outmoded models drawn from psychodynamic theory or treated such dissociative phenomena as purely discursive processes of attributing action and experience to agencies other than the self. Within psychology and psychiatry, understanding of dissociative disorders has been hindered by polemical “either/or” arguments: either dissociative disorders are real, spontaneous alterations in brain states that reflect basic neurobiological phenomena, or they are imaginary, socially constructed role performances dictated by interpersonal expectations, power dynamics and cultural scripts. In this paper, we outline an approach to dissociative phenomena, including trance, possession and spiritual and healing practices, that integrates the neuropsychological notions of underlying mechanism with sociocultural processes of the narrative construction and social presentation of the self. This integrative model, grounded in a cultural neuroscience, can advance ethnographic studies of dissociation and inform clinical approaches to dissociation through careful consideration of the impact of social context.